The Influence Of Operating Cash Flow, Economic Performance And Company Size On Profit Persistence (Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange (BEI) for the 2018-2021 Period) - Ahmad Faiz Zindan Balliyand; Vickrie Khaiqal Dwisstira (STIE Amkop Makassar, 2024)
In this research, quantitative technical methods were used using non-probability methods - purposive sampling. In the purposive sampling sample which focused on this research study, there were 96 company financial reports over a period of 4 years starting from 2018, 2019, 2020 and 2021 from 25 companies that had published their financial reports. In research studied by researchers regarding financial reports in the Property and Real Estate sector for the 2018-2021 period, the results that can be concluded are that operational cash flow has no effect on profit persistence, economic performance has an effect on profit persistence, company size has no effect on profit persistence. Operational cash flow, economic performance and company size simultaneously influence profit persistence.